Features of the Mechanism of Development and Course of Pneumonia When Exposed to Pesticides - Kurambaev Yakhshimurat Bekjanovich; Karimova Sevara Khadjibaevna (Zien Journals, 2022)
The aim of presented work is to study the features of mecha- nism of the development and course of experimental pneumonia against a back- ground of body intoxication by pesticide of OPC - antio group.
Keywords: pesticide; pneumonia; organophosphorus compound; antio